The Roles of Zakat in the Provision of Islamic Social Finance: Qualitative Approach - Mohd Faisol Ibrahim; Aman Shah Siraj (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 354-357